(untitled) (Global Journal of Human-Social Science, 2013)
Marketing of library and information products and services approach aims at determining the needs, wants and demands of the target clients through designing and delivering appropriate products and services more effectively for the purpose of achieving organizational goals and objectives. This paper is an aims to conceptualize the strategic approaches of marketing mix to library and information centers finally, it recognizes some benefits of proposed marketing plan. The librarians should understand the nature of information, needs of users, the transfer process between people and information. Understanding of this new dimension of library and information services will help concerned policy makers in formulating appropriate plans and programs to make the library and information services most effective, and long sustainable.